Ethical concepts in the seventh grade physical education curriculum in Jordan - Abualghanam, Hana Mohammad; Abughanam, Shahed Nasser (Journal of Educational and Psychological Sciences, 2021)
The study aimed to Recognition The importance and development of ethical concepts in the seventh grade physical education curriculum in Jordan. to the results. The study showed the following results:1-There are many ethical concepts that were addressed in the seventh grade physical education curriculum, and the researcher limited them to three concepts, the most prominent of which are (good manners, cooperation, respect), which must be available in such educational curricula. Integration with society, especially at such an age.2-The contribution of the physical education curriculum to the development of moral concepts from the point of view teachers was average This is attributed to the need to pay more attention to these concepts, teach them, and emphasize their application and work. The study recommended focusing on ethical concepts in such contexts.The study recommended the following:1- concentration On Value Moral Islamic in a situation Curricula Education sport. 2- Awareness the society from Through that Education Sports Instrument educational and ethical and back benefit on the students. In addition to suggestions for complementary studies on the subject.
Keywords: Ethical Concepts; Physical Education Curriculum